Modern weapons and military equipment for issue 4/2014 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
China’s latest Yuan-class sub preparing for sea trials Russian Armata MBT trials under way India shows off upgraded Arjun Mk II MBT DCNS pushes Andrasta for Southeast Asia littorals India succesfully tests home-grown Astra AAM